2019
DOI: 10.3389/fonc.2019.01021
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Texture Analysis Based on Breast Magnetic Resonance Imaging in Differentiating Phyllodes Tumors From Fibroadenomas

Abstract: Background: The preoperative diagnosis of phyllodes tumors (PTs) of the breast is critical to appropriate surgical treatment. However, reliable differentiation between PT and fibroadenoma (FA) remains difficult in daily clinical practice. The purpose of this study was to investigate the utility of breast MRI texture analysis for differentiating PTs from FAs.Materials and Methods: Forty-two PTs and 42 FAs were enrolled in this retrospective study. Clinical and conventional MRI features (CCMF) and MRI texture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…This difference was consistent with the literature . However, the mean size of the BPTs (25.1 ± 11.2 mm) in our study was smaller than that reported in the literature (>30 mm) . Mai et al evaluated 42 patients with phyllodes tumors, and Duman et al evaluated 70 patients with phyllodes tumors.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This difference was consistent with the literature . However, the mean size of the BPTs (25.1 ± 11.2 mm) in our study was smaller than that reported in the literature (>30 mm) . Mai et al evaluated 42 patients with phyllodes tumors, and Duman et al evaluated 70 patients with phyllodes tumors.…”
Section: Discussionsupporting
confidence: 91%
“…However, the mean size of the BPTs (25.1 ± 11.2 mm) in our study was smaller than that reported in the literature (>30 mm) . Mai et al evaluated 42 patients with phyllodes tumors, and Duman et al evaluated 70 patients with phyllodes tumors. As mentioned above, patients with suspicious breast lesions are referred to our institution, a tertiary hospital, where BI‐RADS 4A lesions are diagnosed according to grayscale US features, and the lesions are excised as soon as possible.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The results of subsequent studies were similar, and our TA results were no exception, with the AUC, sensitivity, and speci city all lower than those with CRMC, indicating that the diagnostic e ciency of TA alone in NME diagnosis was not high. Some investigators had used TA combined with breast MRI morphology features to distinguish between phyllodes and broadenomas tumors, while others had combined TA with DWI parameters to predict the response to neoadjuvant chemotherapy for breast cancer, and their results demonstrated that combined TA could improve the diagnostic performance [30,31]. On the basis of previous studies, we tried to use the combination of TA and CRMC in NME diagnosis.…”
Section: Discussionmentioning
confidence: 99%